Studies on host factors that regulate the replication of positive strand RNA viruses - Patton, John B. (Kansas State University, 2011)
Positive sense RNA viruses include a diverse group of pathogens that cause a wide array of diseases that can range from sub-clinical to lethal. These viruses infect humans and mammals as well as a variety of other hosts. For their successful replication, viruses interact closely with host cells from the binding to the receptor to the exit as complete viral progenies. During the events, viruses are dependent on host factors for receptor bindings, genome synthesis, and trafficking of viral genome and proteins. Thus there have been major efforts on the studies of understanding the virus-host interactions in the field of virology. In my PhD program, I have studied the host factors that regulate the replication of viruses using porcine reproductive and respiratory syndrome virus (PRRSV) and hepatitis C virus (HCV). I found that modulation of either the viral receptor or cellular signaling pathways had pronounced effects in the replication of PRRSV or HCV respectively. Using PRRSV, I found that the modulation of the level of the putative receptor CD163 on cells with cytokines significantly influence virus replication, suggesting the importance of cytokine presence in environments to determine the replication and pathogenicity of PRRSV via receptor expression in vivo. With HCV, I found that the enhancement of the virus replication occurs through the activation of the epidermal growth factor receptor/extracellular signal-regulated kinase pathway by bile acids which are abundant in the liver where the virus targets in vivo. Furthermore, I found that the bile acid-mediated signaling pathway significantly inhibited the antiviral activities against HCV. These results indicate the importance of environmental factors such as bile acids and signaling pathways in the replication and pathogenicity of HCV in vivo.
Keywords: Porcine reproductive and respiratory syndrome; Hepatitis C virus; CD163; ERK pathway; Virology (0720)